Pengaruh metode dan media pembelajaran terhadap tingkat pengetahuan, keterampilan, kreativitas membuat busana mahasiswa - Srikandi Srikandi; Rika Riwayani; Sukriati Firman (Seminar Nasional LP2M UNM, 2019)
The role of education is to produce quality human resources and possessing knowledge and skills in the field of cloth, of course, can only be obtained through a maximally managed learning process. This study aims to determine the effect of learning methods and learning media on the level of knowledge and skills and their impact on the creativity of making clothes for PKK FT UNM (Family Welfare Education Department, Engineering Faculty, Universitas Negeri Makassar) students. The design of this study used quantitative correlations using path analysis to see direct and indirect causality relationships through intermediary variables and developed into the analysis of Structural Equation Modelling (SEM). The population in this study were all students who had programmed the Course for Making Cloth totalling 135 people. The results of the study showed: (1) The learning method has a significant effect on the level of knowledge but did not affect the skills and creativity of making dresses in the PKK FT UNM students; (2) Learning media does not significantly influence the level of knowledge and skills in making clothes but gives a significant influence on the creativity of making clothes; (3) The level of knowledge has a significant effect on the level of skill and the level of creativity in making clothes at the PKK FT UNM students but the skill level does not significantly influence the creativity of making clothes for PKK FT UNM students.